Synthesis and antimicrobial activity of 3-benzyl-5-methyl-4-oxo-2-thioxo-1,2,3,4-tetrahydrothieno[2,3-d]pyrimidine-6-сarboxylic acid amides - Власов, Сергій Віталійович; Черних, Валентин Петрович (ScienceRise: Pharmaceutical Science, 2016)
Aim. Targeted preparation of the novel antimicrobial agents among the derivatives of 2-thiothieno[2,3-d]pyrimidine-6-carboxylic acids. Materials and methods of research. The routine methods of organic synthesis and structural chemistry, the screening methods recommended by WHO for antimicrobial activity studies were used for this work. Results. The series of the novel amides of 3-benzyl-5-methyl-4-oxo-2-thioxo-1,2,3,4-terahydrothieno[2,3-d]pyrimidine-6-carboxylic acid has been performed using the 1,1’-carbonyldiimidazole promoted interaction of the corresponding acid with amines in the DMF media and their antimicrobial activity was studied. Conclusions. The study for the amides obtained allowed identification of some derivatives with the wide range of antibacterial activity and no influence on the growth of Candida fungi; the ethyl ester of 3-benzyl-5-methyl-4-oxo-2-thioxo-1,2,3,4-terahydrothieno[2,3-d]pyrimidine-6-carboxylic acid was found to be the most active compound against the strains of Bacillus subtilis and Candida albicans